English pronunciation in intermediate use - Hancock, Mark (University Press, 2003)
English Pronunciation in Use is for learners of intermediate level and above. The material is addressed to the individual learner who may be working alone, but it can also be used in the classroom. This book covers all aspects of pronunciation including individual sounds, word stress, connected speech and intonation. English Pronunciation in Use recognises the importance of pronunciation for listening as well as speaking and learners are provided with both receptive and productive practice. English Pronunciation in Use * 60 easy-to-use two-page units: explanations and examples of key pronunciation points are presented on left-hand pages with a range of exercises on facing right-hand pages. * Audio components: all the examples and exercises are recorded and available on audio CD. * Clear model for repetition: a single British accent is used as a model for learners to listen to and repeat. * Exposure to different accents: learners are given the opportunity to listen to a range of different English accents and learn about their similarities and differences. * Self-diagnostic test: helps learners identify their own pronunciation problems. * Additional reference section: including fun exercises to practice phonemic symbols, a guide for speakers of specific languages, exercises on minimal pairs and a glossary of specialised terms. * Learner-friendly answer key.